Glycan Masking of Epitopes in the NTD and RBD of the Spike Protein Elicits Broadly Neutralizing Antibodies Against SARS-CoV-2 Variants - Lin, Wei-Shuo; Chen, I-Chen; Chen, Hui-Chen; Lee, Yi-Chien; Wu, Suh-Chin (Frontiers in Immunology, 2021)
Glycan-masking the vaccine antigen by mutating the undesired antigenic sites with an additional N-linked glycosylation motif can refocus B-cell responses to desired epitopes, without affecting the antigen’s overall-folded structure. This study examined the impact of glycan-masking mutants of the N-terminal domain (NTD) and receptor-binding domain (RBD) of SARS-CoV-2, and found that the antigenic design of the S protein increases the neutralizing antibody titers against the Wuhan-Hu-1 ancestral strain and the recently emerged SARS-CoV-2 variants Alpha (B.1.1.7), Beta (B.1.351), and Delta (B.1.617.2). Our results demonstrated that the use of glycan-masking Ad-S-R158N/Y160T in the NTD elicited a 2.8-fold, 6.5-fold, and 4.6-fold increase in the IC-50 NT titer against the Alpha (B.1.1.7), Beta (B.1.351) and Delta (B.1.617.2) variants, respectively. Glycan-masking of Ad-S-D428N in the RBD resulted in a 3.0-fold and 2.0-fold increase in the IC50 neutralization titer against the Alpha (B.1.1.7) and Beta (B.1.351) variants, respectively. The use of glycan-masking in Ad-S-R158N/Y160T and Ad-S-D428N antigen design may help develop universal COVID-19 vaccines against current and future emerging SARS-CoV-2 variants.